Surveying: Profession And Professionalism - Subedi, Nab Raj (Journal on Geoinformatics, Nepal, 2007)
Surveying profession has been very dynamic in nature in recent times.. Like other professions such as medical, engineering, teaching, pharmacy etc., surveying profession has acquired its own dimension guided by functionalities and specification plus standard. A surveyor is a surveyor irrespective of nationalities, race and origin. Though development of technologies in the domain of surveying has of course necessitated surveyors of modern world to be more frequently updated in terms of skill and capabilities to adapt him/herself in the new environment, the basic objectives yet remains the same in the profession of surveying. Today anyone can assume him/herself being as a surveyor by just using the latest tools of earth observation but prior to proclaiming oneself as a surveyor, one must rethink whether the proclaimer inherits or holds the basic qualification in terms of education, professional requirement and his/her state's rule and regulation or law pertaining to the profession.